1976
DOI: 10.1161/01.res.38.3.172
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations of the left ventricle to chronic pressure overload.

Abstract: SUMMARY Left ventricular (LV) function during the adaptationto chronic pressure overload produced by an ascending aortic constriction was analyzed in conscious dogs, instrumented with intraventricular micromanometers and pairs of ultrasonic crystals for measurement of LV wall thickness (WTh) and internal LV chamber diameter. During inflation of the cuff to produce LV pressures averaging 220 mm Hg, calculated peak wall stress (WSt) increased by 55% above control while percent shortening decreased by 24% and mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(52 citation statements)
references
References 35 publications
4
45
0
Order By: Relevance
“…Since this increase also was found for minimal late diastolic resistance, it probably was not due directly to increased myocardial compression in systole. If our dogs with hypertrophy were similar to those studied by Sasayama et al, 15 then the changes of minimal resistance that we observed cannot be explained by increased ventricular volumes or wall tensions, since these were normal in their study.…”
Section: Discussionsupporting
confidence: 85%
“…Since this increase also was found for minimal late diastolic resistance, it probably was not due directly to increased myocardial compression in systole. If our dogs with hypertrophy were similar to those studied by Sasayama et al, 15 then the changes of minimal resistance that we observed cannot be explained by increased ventricular volumes or wall tensions, since these were normal in their study.…”
Section: Discussionsupporting
confidence: 85%
“…Sasayama and colleagues assessed LV responses to ascending aortic banding in conscious dogs by utilizing intraventricular micromanometers and ultrasonic crystals for measurement of LV wall thickness and internal chamber diameter. They found that the LV initially dilates in response to elevated pressure due to increased wall stress [9]. This acute response is followed by gradual wall thickening and consequent reductions in wall stress to near normal levels, thereby preserving normal LV chamber size and inotrope [9].…”
Section: Compensatory LV Response To Asmentioning
confidence: 99%
“…They found that the LV initially dilates in response to elevated pressure due to increased wall stress [9]. This acute response is followed by gradual wall thickening and consequent reductions in wall stress to near normal levels, thereby preserving normal LV chamber size and inotrope [9].…”
Section: Compensatory LV Response To Asmentioning
confidence: 99%
“…limit wall stress and preserve systolic function [8]. However, ultimately, severe afterload causes a fall in left ventricular ejection fraction even in the presence of relatively preserved contractility.…”
Section: Opinion Statementmentioning
confidence: 99%